A revision of the spider genus Orthobula Simon, 1897 (Araneae: Trachelidae) in the Afrotropical Region. I. Continental species - Haddad, Charles R.; Jin, Chi; Platnick, Norman I. (Zootaxa, 2022)
The continental Afrotropical species of the spider genus Orthobula Simon, 1897 are revised. The three currently known species, O. calceata Simon, 1897 (West Africa and western Congo Basin), O. milloti Caporiacco, 1949 (Kenya) and O. radiata Simon, 1897 (southern Africa), are redescribed, including the first descriptions of the males of O. calceata and females of O. radiata. Three new species are described from both sexes: O. aethiopica sp. nov. from Ethiopia, O. arca sp. nov. from South Africa, and O. marusiki sp. nov. from West Africa and the western Congo Basin. All of the species are obligate ground-dwellers, being particularly common in the leaf litter of woody plants, except for O. arca sp. nov., which prefers open grasslands.